(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2023)
When the socio-economic forces (basically those serving the capitalist mode of production) rule human beings, common people lose their agency, or the people in the upper strata tend to overlook, suppress and even suspend the agencies of people at the bottom level. We have evidences of the mockery of the writers and composers towards the soldiers and rebels deprived of their agencies. On the other hand, the aesthetics of human agency in subjugated people like soldiers and rebels is a relevant area of study. How do the contemporary Nepali paintings depict such theme is still a researchable gap. This paper investigates how contemporary paintings by some Nepali artists deal with the suspension of agency, subaltern consciousness and dissolution of humanity with regards to the lives of rebels (the ex-fighters of Maoist Peoples War in Nepal) and soldiers (British Gorkha soldiers). The discussion predominantly builds on the paintings ‘Gurkhas: Decoratively Tightened for Last 200 Years’ and ‘Bravery in the Box’ by Sunil Sigdel followed by ‘A Rebel Turned Gulf Migrant’ by Hitman Gurung, though not limited to these works. The discussion largely incorporates theoretical and conceptual implements from relevant literature on agency theories, resistance and body aesthetics, such as the ideas of Michael Garnett, Kasper Masse, Margaret S. Archer and others. The method of discussion is predominantly critical analysis of the selected paintings, personal interviews with the artists, and socio-political reverberations these works have created as reflected in some secondary texts like show feedback in visitor’s book, reviews in published in media, preface articles in exhibition brochures, etc. The findings of the discussion suggest absence and inhuman suspension of agencies in Gorkha Soldiers and Ex-Rebels. The paper concludes affirming the scope and nature of the aesthetics of human agency, especially focusing on the practice of deep agency.